The effect of mat layers moisture content on some properties of particleboard : Utjecaj sadržaja vode u slojevima ploče iverice na njezina svojstva - Istek, Abdullah (Array, 2019)
In this study, the effect of mat moisture content on the physical and mechanical properties of particleboard was investigated. The experimental boards were produced by using 40 % softwood, 45 % hardwood chips, and 15 % sawdust. The formaldehyde resin/adhesive was used in three-layers (bottom-top layer 12 %, core layer 8 %). Multi-opening press was used during manufacturing the experimental particleboards. The physical and mechanical properties of boards obtained were identified according to the TS-EN standards. The optimum core layer moisture content was determined as 6 % and 7 % according to the results, whereas the moisture content of bottom and top layers was 14 %. Under these moisture content conditions, the bending strength was found to be 13.3 N/mm², the modulus of elasticity in bending 2466 N/mm², and internal bonding strength 0.44 N/mm². The optimum bottom-top layer moisture content was determined to be between 13 % and 15 % and 6.5 % for the core layer.